Increasing productivity and sustaining the rice based production system through Farmer FIRST approach - Mishra, S K; Das, Lipi; Chahal, V P; Lenka, S; Satapathy, B S; Giri, S C; Acharya, G C; Prangya, Swatee; Jena, K B; Jethy, Sonali (Indian Farming, 2022)
.